2022
DOI: 10.31893/jabb.22031
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the melatonin receptor 1A (MTNR1A) gene affect the sexual performance of Rasa Aragonesa rams without changing their social dominance

Abstract: This study aimed to investigate whether a specific genotype of the MTNR1A gene influences social dominance and reproductive performance in rams. Thirty-one rams were genotyped for Rsal and Mnll polymorphism of the gene: CC (n=19), CT (n=5), and TT (n=7), and GG (n=20), GA (n=6), or AA (n=5), respectively. Maintenance (standing still, lying down, drinking, feeding, walking, or stereotyping) and social behavior (agonistic and antagonistic interactions among rams) were recorded by direct observations involving in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…5,22 Despite the fact that the ramifications of the MTNR1A gene on reproductive seasonality have only been investigated to a limited extent up until this point, those studies have shown that these effects are tied to three specific mutations discovered in exon II at locations 606, 612, and 706, 7,21 only sheep of the Sarda and Aragonese breeds have had the remaining portions of this gene examined. 12,13,[23][24][25] Mechanisms Involved in the Production and Secretion Control of Melatonin The pineal gland predominantly secretes melatonin during nocturnal hours, thereby designating this hormone as an inherent informant of the photoperiodic trend. 26 The circadian influence of melatonin is orchestrated through melatonin receptors located in the hypothalamic suprachiasmatic nucleus, the central hub of the circadian clock.…”
Section: Mtnr1a Locationmentioning
confidence: 99%
“…5,22 Despite the fact that the ramifications of the MTNR1A gene on reproductive seasonality have only been investigated to a limited extent up until this point, those studies have shown that these effects are tied to three specific mutations discovered in exon II at locations 606, 612, and 706, 7,21 only sheep of the Sarda and Aragonese breeds have had the remaining portions of this gene examined. 12,13,[23][24][25] Mechanisms Involved in the Production and Secretion Control of Melatonin The pineal gland predominantly secretes melatonin during nocturnal hours, thereby designating this hormone as an inherent informant of the photoperiodic trend. 26 The circadian influence of melatonin is orchestrated through melatonin receptors located in the hypothalamic suprachiasmatic nucleus, the central hub of the circadian clock.…”
Section: Mtnr1a Locationmentioning
confidence: 99%